Analisa Pengaruh Pembebanan untuk Peramalan Umur Trafo Study Kasus pada PT. PLN UP3 Surabaya Barat - Wati, Trisna; Saputra, Fiqih Bayu; Isyraqi, Fariz; Sukryawan, Yoga (Institut Teknologi Adhi Tama Surabaya, 2023)
In the five distribution transformers operating in 2020–2022, the load has increased in each period. At the RA 1208 substation, the load during the day is 9.7% and 8.33% at night. The RA 1218 substation has a load during the day of 6.47% and 4.15% at night. RB substation has loads of 5.93% during the day and 6.55% at night. The RA 1220 substation gets loads of 4.78% during the day and 4.13% at night. RA 977 substation obtains loads of 7.27% during the day and 6.02% at night. Load improvement, causing heat and loss of life, is influenced by ambient temperature, where the average daily temperature in Surabaya reaches 29°C to 30°C. In order to make the transformer at PLN Ltd. UP3 in West Surabaya work properly, it is necessary to predict the transformer’s life. This study employed linear and exponential trends, with the MAPE evaluation test and impact analysis of the loading on the transformer's remaining life referring to IEC standards. At substation 1208 and using an exponential trend of 1.2597%, the remaining life forecast for 2032 is 7.92 years. Substation 1218, using an exponential trend of 1.2361%, has a remaining life forecast of 10.81 years. With an exponential trend of 1.1048%, substation RB 1503 gains a remaining life forecast of 10.52 years. Substation 1220, using an exponential trend of 1.2057%, gets a remaining life forecast of 10.95 years. Substation RA 977, using the exponential trend of 1.6338%, has a remaining life forecast of 6.46 years.